Money demand and macroeconomic stability revisited - Andreas Schabert; Christian Stoltenberg (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
This paper examines how money demand induced real balance effects contribute to the determination of the price level, as suggested by Patinkin (1949,1965), and if they affect conditions for local equilibrium uniqueness and stability. There exists a unique price level sequence that is consistent with an equilibrium under interest rate policy, only if beginning-of-period money enters the utility function. Real money can then serve as a state variable, implying that interest rate setting must be passive for unique, stable, and non-oscillatory equilibrium sequences. When end-ofperiod money provides utility, an equilibrium is consistent with infinitely many price level sequences, and equilibrium uniqueness requires an active interest rate setting. The stability results are, in general, independent of the magnitude of real balance effects, and apply also when prices are sticky. In contrast, under a constant money growth policy, equilibrium sequences are (likely to be) locally stable and unique for all model variants. Keywords: Real balance effects ; predetermined money ; price level determination ; real determinacy ; monetary policy rules
Keywords: E32; E41; E52; 330; Geldnachfrage; Geldpolitik; Regelgebundene Politik; Realkasseneffekt